Optimized Automatic Fault Electrode Management of Structural Health Monitoring of Aircraft Composites - Ngoc, Nam Pham; Leuchter, Jan; Blasch, Erik (IEEE (Institute of Electrical and Electronics Engineers), 2024)
Detecting the structural integrity of composite material used in an airframe includes passive nondestructive testing (NDT) and active electrical impendence tomography (EIT). EIT benefits enhance real-time response and accuracy but require pragmatic approaches to analyze the electrode errors from faulty or nonresponsive readings. The nonfunctional connections of measuring electrodes often occur during onboard aircraft operations for various reasons, such as deterioration. The deterioration of the electrode impedance impacts the quality of the EIT reconstructed image. This article compares different EIT methods and proposes surface fault detection EIT (SURFEIT). The proposed SURFEIT techniques that detect and compensate for faults are verified and evaluated using models with different locations of inside damages. Results prove the effectiveness of SURFEIT techniques, when the number of faulty electrodes is up to one-fourth of the total electrodes. The biggest benefit of the SURFEIT techniques is that they do not require any additional simulation work, lead to significant reduction of computation time, and afford very fast indications of damage locations.
Automatické diagnostikování poruchových elektrod při monitorování stavu leteckých kompozitů
Keywords: Data compensation; electrical impedance tomography (EIT); manage faulty electrodes; Monitorování stavu kompozitu, EIT,